Perceived Stress and Norepinephrine Predict the Effectiveness of Response to Protease Inhibitors in HIV - Ironson, Gail (2008)
BACKGROUND: In vitro evidence has suggested that increasing levels of norepinephrine (NE) can accelerate HIV replication; however, the importance in a clinical setting has not been tested. PURPOSE: The purpose of this study was to determine if perceived stress as well as the stress hormones NE and cortisol would predict the response to starting a new protease inhibitor (PI) prospectively. METHOD: Perceived stress, urinary cortisol and norepinephrine, CD4 and viral load (VL) were measured in people with HIV before starting a new PI and six months later (an average of three months after starting the new PI) in order to determine CD4 and VL response to the PI. RESULTS: Higher perceived stress significantly predicted lower effectiveness of the new PI in increasing CD4 and decreasing VL controlling for age, duration of new PI, baseline CD4/VL, sexually transmitted diseases (STDs), and gender/ethnic risk groups. Higher norepinephrine, but not cortisol, predicted worse VL response to PIs and, in fact, mediated the relationship between perceived stress and change in VL. CONCLUSION: Perceived stress and high norepinephrine levels are prospectively associated with a poorer response to starting a new PI. Assessing stress and norepinephrine levels in patients starting on antiretroviral medications might be clinically useful.